2022
DOI: 10.1101/2022.09.27.507129
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The fitness of an introgressing haplotype

Abstract: The genomic era has made clear that introgression, or the movement of genetic material between species, is a common feature of evolution. Examples of both adaptive and deleterious introgression exist in a variety of systems. What is unclear is how the fitness of an introgressing haplotype changes as species diverge, or as the size of the introgressing haplotype changes. In a simple model, we show that early in the process of divergence, introgression of large haplotypes can be favored more than introgression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Although the karyotypic diversification of guenons may have altered their recombination landscape, heterozygosity is still expected to be elevated in introgressed regions in the admixed lineage (but not necessarily globally). However, a recent theoretical study suggested that the relationship between recombination and introgression rates may be absent or negative in the early stages of species divergence and only later become positive (Dagilis and Matute 2022). Two out of four events lacking this relationship occurred between closely related lineages (F and G, diverged < 2 My before hybridization) and may thus not have been diverged enough to develop the positive relationship between recombination and introgression.…”
Section: Discussionmentioning
confidence: 99%
“…Although the karyotypic diversification of guenons may have altered their recombination landscape, heterozygosity is still expected to be elevated in introgressed regions in the admixed lineage (but not necessarily globally). However, a recent theoretical study suggested that the relationship between recombination and introgression rates may be absent or negative in the early stages of species divergence and only later become positive (Dagilis and Matute 2022). Two out of four events lacking this relationship occurred between closely related lineages (F and G, diverged < 2 My before hybridization) and may thus not have been diverged enough to develop the positive relationship between recombination and introgression.…”
Section: Discussionmentioning
confidence: 99%